ANALISIS PENERAPAN STANDAR AKUNTANSI KEUANGAN ENTITAS TANPA AKUNTABILITAS PUBLIK (SAK ETAP) NO.1 TENTANG PENYAJIAN LAPORAN KEUANGAN PADA PT AGRI MANDIRI LESTARI JAKARTA SELATAN - Kusuma, Indra Cahya; Ruslan, Ruslan; Triwidatin, Yuppi (Komunitas Manajemen Kompetitif, 2024)
This study aims to determine andaanalyze the applicationnof Financial Accountingg Standards for Entities Without Public Accountability (SAK ETAP)” N0.1 in .pthe presentation of financial, statements at PT. Agri Mandiri Lestari, South Jakarta. “This type of research is a case study”. The research. method of data analysis “in this study used a qualitative descriptive method”. Data collectionntechniques used by the author are interviews, documentation. “The results of the analysis that have been carried out show that the, “application of financial accounting ‘standards presented in the financial statements’of PT. Agri Mandiri Lestari refers to SAK ETAP No.1 has not been in, accordance with what has been .regulated. “The preparation of the financial statements of “PT. Agri Mandiri Lestari only sconsists of a balance sheet and income statementt. In addition to the incomplete components oof the financial statementss, there are items in the financial statements that are not appropriate, such as the placement of items, differences in the use of the established method and items that should be included in tthe financial statementss but are not presented, in the financial statements Keywords: SAK ETAP No.1, Financial Report, PT Agri Mandiri Lestari